Despite the Insufficiency of Extension Workers, Farmer Satisfaction with Extension Worker Performance Remains High - Unang; Burhan Sidqi; Tenten Tedjaningsih (PT FORMOSA CENDEKIA GLOBAL, 2022)
Insufficient agricultural extension workers emerge in Indonesia to meet the demand for agricultural extension workers in the field. The COVID-19 outbreak has worsened the situation because extension workers lack proper guidance. This study aimed to determine how satisfied farmers are with the performance of agricultural extension workers. The case study was carried out at the Purwadadi District Agricultural Extension Center in the Ciamis Regency of West Java, Indonesia. The performance of extension workers was assessed using Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). According to the findings of the study, the relevance of the characteristics tangible, reliability, alertness, assurance, and empathy falls under the category of extremely vital. In terms of tangible, responsiveness, and assurance, as well as empathy and reliability, the farmers reported that the performance of agricultural workers remained outstanding. Additionally, the farmers were satisfied with the overall performance of the agricultural extension workers. The extension workers' abilities to guide the farmers' learning process with precision and clarity, as well as their understanding of field challenges, must be improved.